IMPLEMENTASI PENDIDIKAN KARAKTER DI SEKOLAH DASAR: UPAYA PENDIDIK MEMBENTUK KARAKTER SISWA DALAM MEMPERSIAPKAN GENERASI EMAS 2045 BERBASIS NEUROSAINS - Usan Usan; Suyadi Suyadi (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2022)
Education is absolutely necessary for humans, because it is an effort to shape character. This is inseparable from the role of parents and teachers. Parents as the first teachers, forming character is an obligation not only at birth, but when the baby is in the womb. In addition, teachers, especially in elementary schools, have the same obligation in shaping character. In the process, teachers need to use a brain-based character education approach (neuroscience). The reason is that the success of forming character starts from changing the student's brain. If brain-based character education is applied from an early age, the implication is that Indonesian education is of higher quality and able to prepare a quality 2045 golden generation. This research uses qualitative research based on literature review. Based on the results of the study, it was found that quality education is education that is able to shape the character of its students. Character education is more effective if it uses a brain approach (neuroscience), because changing character begins by changing the student's brain